Sistema de ecuaciones lineales a + b = 135 + a – b = - 35

a + b = 135 a – b = -35

2a a a

x + y = 72 x – y = 48

= 100 = 100 2 = 50

x + y = 72 + x – y = 48 2x x x

= 120 = 120 2 = 60

(5) 2x + 9y = 39 (-2) 5x – y = -20

2x + 9y = 39 5x – y = -20 +

10x + 45y = 195 -10x + 2y = 40 47y = 235 y = 235 47 y =5

(4) 5x + 2y = 24 (-5) 4x + 3y = 29

5x + 2y = 24 4x + 3y = 29 +

20x + 8y = 96 -20x – 15y = -145 -7y = -49 -y = -49 7 -y = -7 y=7

a + b = 135 50 + b = 135 b = 135 – 50 b = 85

x + y = 72 60 + y = 72 y = 72 – 60 y = 12

2x + 9y = 39 2x + 9(5) = 39 2x + 45 = 39 2x = 39 – 45 2x = -6 x=2 -6 x = -3

5x + 2y = 24 5x + 2(7) = 24 5x + 14 = 24 5x = 24 – 14 5x = 10 x = 10 5 x=2

a = 50 b = 85

x = 60 y = 12

x = -3 y=5

x=2 y=7

(7) 8x - 3y = 17 (-8) 7x - 4y = 8

8x - 3y = 17 7x - 4y = 8 +

56x - 21y = 119 -56x + 32y = -64 11y = 55 y = 55 11 y=5 (3) 8x + y = 21 (8-) 3x + y = 11

8x + y = 21 3x + y = 11 +

24x + 3y = 63 -24x - 8y = -88 -5y = -25 -y = -25 5 -y = -5 y=5 (4) 5x – 2y = 31 (-5) 4x + 3y = 11

5x – 2y = 31 4x + 3y = 11 +

20x - 8y = 124 -20x - 15y = -55 -23y = 69 -y = 69 23 -y = 3 y = -3 (1) 5x – 6y = 21 (-5) x - 2y = 5

5x – 6y = 21 x - 2y = 5 +

5x - 6y = 21 -5x + 10y = -25 4y = -4 y = -4 4 y = -1

8x - 3y = 17 8x - 3(5) = 17 8x - 15 = 17 8x = 17 + 15 8x = 32 x = 32 8 x=4 8x + y = 21 8x + 5 = 21 8x = 21 - 5 8x = 16 x = 16 8 x=2

5x – 2y = 31 5x – 2(-3) = 31 5x + 6 = 31 5x = 31 - 6 5x = 25 x = 25 5 x=5

5x – 6y = 21 5x – 6(-1) = 21 5x + 6 = 21 5x = 21 - 6 5x = 15 x = 15 5 x=3

x=4 y=5

x=2 y=5

x=5 y = -3

x=3 y = -1